Atomically Dispersed Single Co Sites in Zeolitic Imidazole Frameworks Promoting High‐Efficiency Visible‐Light‐Driven Hydrogen Production. Issue 41 (1st July 2019) - Ran, Jingrun; Zhang, Hongping; Qu, Jiangtao; Xia, Bingquan; Zhang, Xuliang; Chen, Shuangming; Song, Li; Jing, Liqiang; Zheng, Rongkun; Qiao, Shi‐Zhang
Abstract: As photocatalysis technology could transform renewable and clean solar energy into green hydrogen (H2 ) energy through solar water splitting, it is regarded as the "Holy Grail" in chemistry field in the 21st century. Unfortunately, the bottleneck of this technique still lies in the exploration of highly active, cost‐effective, and robust photocatalysts. This work reports the design and synthesis of a novel zeolitic imidazole framework (ZIF) coupled Zn0.8 Cd0.2 S hetero‐structured photocatalyst for high‐performance visible‐light‐induced H2 production. State‐of‐the‐art characterizations and theoretical computations disclose that the interfacial electronic interaction between ZIF and Zn0.8 Cd0.2 S, the high distribution of Zn0.8 Cd0.2 S on ZIF, and the atomically dispersed coordinately unsaturated Co sites in ZIF synergistically arouse the significantly improved visible‐light photocatalytic H2 production performance. Abstract : Noble‐metal‐free H2 production : The novel Zn0.8 Cd0.2 S coupled zeolitic imidazole framework composite exhibits a greatly enhanced visible‐light photocatalytic H2 production activity owing to the synergistic effects of strong electronic coupling, high dispersion of Zn0.8 Cd0.2 S, and the atomically dispersed single Co sites in the zeolitic imidazole framework.